Pengaruh Disiplin Kerja terhadap Kinerja Karyawan PT Pendekar Bodoh (D'cost) - Dona Fitria; Burhanudin Burhanudin; Nurlaela Nurlaela (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
This study aims to determine the effect of work discipline on the performance of employees of PT. Pendekar Bodoh (Dcost). The method used is a quantitative method. The population is employees of PT. The Stupid Swordsman (Dcost) totaling 125 people and the sample taken as many as 95 people using the "Simple Random Sampling" technique. The regression equation obtained is Y = 20.60 + 0.60 X. Based on hypothesis testing, it is obtained that t count is 5.641 > 1.986, which is greater than t_table which is 1.986. So Ho is rejected and Ha is accepted. It can be concluded that there is a significant influence between work discipline on employee performance at PT. Pendekar Bodoh (Dcost). Based on the calculation, the correlation coefficient value is 0.5, which means that there is a positive and quite strong correlation between work discipline and employee performance. Based on the calculation results, the coefficient of determination (KD) value is 25.5%, this means that employee performance is influenced by work discipline by 25.5% while the remaining 74.5% employee performance is influenced by other factors that have not been studied.